Family presence during resuscitation in emergency departments: professionals' attitudes in Brazil. (12th October 2018) - Barreto, M.S.; Garcia‐Vivar, C.; Mitchell, M.; Marcon, S.S.
Abstract : Aim: The study explored the views and attitudes of nurses and physicians on family presence during resuscitation in emergency departments in Brazil. Background: International emergency associations endorse family presence during resuscitation; however, the extent to which it is practiced remains unclear, particularly in the Brazilian context. Research of emergency staff views and attitudes towards this practice is desirable so that actions can be identified to support families at the bedside. Methods: A qualitative research was conducted. Thirty‐two health professionals (11 physicians and 21 nurses) working in two emergency departments in southern Brazil were purposefully recruited in January 2015. In‐depth interviews were conducted, and data were analysed using content analysis. Findings: Nurses and physicians found family presence during resuscitation controversial and the general attitude towards this practice was negative. They reported that 'changes are needed' to adapt hospital infrastructures for family presence, and to train staff to respond to the information and emotional needs of families. Discussion: Translating a family nursing framework into clinical practice involves the need for reassessing educational and management policies in clinical contexts. Conclusion: This research brings new understanding about the attitudes of some Brazilian nurses and physicians on the implementation of family presence during resuscitation and identifies the need to develop policies and strategies to improve family presence in emergency departments. Implications for nursing and health policy: Hospital‐based policies are required to improve family‐centred care in emergency departments while providing a criterion of legality and safety to professionals to invite families to be present during invasive procedures. Also, family‐focused education in health science degrees, continuing education and in the community is required.